Coopetição entre cooperativas de crédito e fintechs: construindo os fatores de cooperação por meio da grounded theory - Scaravonatto, Maicon (Universidade do Vale do Rio dos Sinos, 2018)
The financial services market has undergone changes with the emergence of the new lean companies (startups). The operating and innovation models of these companies brings, to this day, technological innovations and different ways of relating to customers. The Brazilian financial ecosystem is undergoing a new paradigm, in which information technology is driving innovation in the sector. Thereby, the Fintech phenomenon has been gaining strength within the market. On the other hand, there is a phenomenon called Credit Unions, which are leaders in customer retention. The business model of cooperatives goes far beyond a simple banking transaction. To the society, it is characterized by a process of access to financial services, assuming the corresponding risks and generating benefits for the local community. The present research has, as a background, these two phenomena. The research was carried out using the Grounded Theory scientific method and sought to discover the cooperation factors between Credit Unions and Fintechs. The construction of the grounded theory proposed a theoretical framework, by the credit union point of view. The results of the cooperation factors presented in the theoretical framework emerged through the Grounded Theory, by the diagnoses of the theoretical foundation and the references from the empirical field. The main contribution was to assert that it is possible to make Coopetition between the two phenomena.
Keywords: Coopetição; Grounded theory; Cooperativas de crédito; Fintech; Coopetition; Grounded theory; Credit unions; Fintech; ACCNPQ::Ciências Sociais Aplicadas::Administração